2016
DOI: 10.1021/acs.jafc.6b00968
|View full text |Cite
|
Sign up to set email alerts
|

Different Lipopolysaccharide Branched-Chain Amino Acids Modulate Porcine Intestinal Endogenous β-Defensin Expression through the Sirt1/ERK/90RSK Pathway

Abstract: Nutritional induction of endogenous antimicrobial peptide expression is considered a promising approach to inhibit the outgrowth and infection of pathogenic microbes in mammals. The present study investigated possible regulation of porcine epithelial β-defensins in response to branched-chain amino acids (BCAA) in vivo and in vitro. BCAA treatment increased relative mRNA expression of jejunal and ileal β-defensins in weaned piglets. In IPEC-J2 cells, isoleucine, leucine, and valine could stimulate β-defensin ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 47 publications
(98 reference statements)
1
52
0
Order By: Relevance
“…For example, glutamine, arginine, and threonine could improve integrity of tight junctions, cell migration, anti-oxidative responses, and mucosal barrier functions in the intestine [ 74 ]. Likewise, BCAAs also act as a regulator to promote intestinal development, nutrient transporters, and immune-related function and then improve gut health [ 75 , 76 , 77 ]. However, most of the studies focus on the Leu functions but not Val or Ile in the intestine.…”
Section: Physiological Functions Of Bcaas On Intestinal Health Andmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, glutamine, arginine, and threonine could improve integrity of tight junctions, cell migration, anti-oxidative responses, and mucosal barrier functions in the intestine [ 74 ]. Likewise, BCAAs also act as a regulator to promote intestinal development, nutrient transporters, and immune-related function and then improve gut health [ 75 , 76 , 77 ]. However, most of the studies focus on the Leu functions but not Val or Ile in the intestine.…”
Section: Physiological Functions Of Bcaas On Intestinal Health Andmentioning
confidence: 99%
“…BCAAs may enhance disease resistance and intestinal health through modulation of endogenous defensin in young animals and children. Ren et al [ 76 ] investigated the mRNA expression of porcine epithelial β-defensins in response to BCAAs. The results indicated that BCAAs treatment increased the expression of β-defensins in jejunum and ileum of weaned piglets, and the similar stimulate effect of BCAAs on β-defensin expression was found in IPEC-J2 cells.…”
Section: Physiological Functions Of Bcaas On Intestinal Health Andmentioning
confidence: 99%
“…Isoleucine is a kind of branched chain amino acid, which is essential for some physiological functions of humans and pigs ( 7 , 9 11 ). Burns ( 9 ) has shown that isoleucine will specifically be incorporated into proteins of immune cells, such as lymphocytes, eosinophils, and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…The use of pigs as an animal model for translational research focusing on β‐defensins and infectious diseases is growing (Alizadeh et al, ; Bao et al, ; Liu et al, ; Ren et al, ; Tang et al, ; X. Yang et al, ). The messenger RNA (mRNA) expression of thirteen different porcine β‐defensins has been described in several tissues (G. Zhang et al, ; Sang, Patil, Zhang, Ross, & Blecha, ) and, with regard to the transcriptomics of the swine epididymis, seven β‐defensins showed marked regionalized expression, including the porcine β‐defensins 3 (pBD3), 4 (pBD4), 125 (pBD125) and epididymal protein splicing variant 2C (pEP2C; Guyonnet, Dacheux, Dacheux, & Gatti, ).…”
Section: Introductionmentioning
confidence: 99%